Coronavirus Disease 2019 and Human Reproduction: A Changing Perspective (Clinics, 2021)
Since the outbreak of severe acute respiratory coronavirus 2 (SARS-CoV-2), the coronavirus disease 2019 has had a wide range of effects on human health. This paper summarizes the data related to the effects of the SARS-CoV-2 infection on human reproduction.Both the male and female reproductive tract express high levels of receptors and proteins needed for viral cell entry. There is presently no evidence that gametes are affected by the infection. Male fertility may be temporarily reduced due to inflammatory responses following infection. The endometrium is highly susceptible to SARS-CoV-2 cell entry; however, it remains unclear whether this could alter receptivity and embryo implantation. Menstrual cycle changes were reported in women who experienced severe infection; however, they tended to be reversible. For couples undergoing assisted reproduction treatment, the pandemic led to a significant psychological burden, with changes in lifestyle that could directly affect the success of the treatment. Human reproduction societies recommend screening all patients prior to cycle initiation and avoiding treatment of women with severe comorbidities until the pandemic is under control. Finally, for pregnant women, it is expected that the infection is more severe in women in the third trimester and in those with comorbidities. Those who are symptomatic for SARS-CoV-2 are more likely to have increased rates of prematurity and intrapartum fetal distress than those who are asymptomatic. Vertical transmission cannot be completely ruled out, but neonatal infection rates are low. Vaccination appears to be safe and is indicated for use in pregnant and lactating women because the benefits outweigh the risks.